Genetic knockout of the α7 nicotinic acetylcholine receptor gene alters hippocampal long-term potentiation in a background strain-dependent manner. (3rd August 2016) - Freund, Ronald K.; Graw, Sharon; Choo, Kevin S.; Stevens, Karen E.; Leonard, Sherry; Dell'Acqua, Mark L.
Highlights: Both α7nAChR function and genetic background are important in schizophrenia. C57/Bl6 and C3H mice differ in background expression of α7nAChRs (C3H > C57). Knockout of the α7nAChR gene impaired LTP in C3H but not C57 mice. C3H knockout mice displayed abnormal auditory gating, a schizophrenic phenotype. Genetic background strongly influences phenotypic expression in schizophrenia. Abstract: Reduced α7 nicotinic acetylcholine receptor (nAChR) function is linked to impaired hippocampal-dependent sensory processing and learning and memory in schizophrenia. While knockout of the Chrna7 gene encoding the α7nAChR on a C57/Bl6 background results in changes in cognitive measures, prior studies found little impact on hippocampal synaptic plasticity in these mice. However, schizophrenia is a multi-genic disorder where complex interactions between specific genetic mutations and overall genetic background may play a prominent role in determining phenotypic penetrance. Thus, we compared the consequences of knocking out the α7nAChR on synaptic plasticity in C57/Bl6 and C3H mice, which differ in their basal α7nAChR expression levels. Homozygous α7 deletion in C3H mice, which normally express higher α7nAChR levels, resulted in impaired long-term potentiation (LTP) at hippocampal CA1 synapses, while C3H α7 heterozygous mice maintained robust LTP. In contrast, homozygous α7 deletion in C57 mice, which normally express lower α7nAChR levels, did not alter LTP, as had been previously reported for this strain. Thus, the threshold of Chrna7 expression required for LTP may be different in the two strains. Measurements of auditory gating, a hippocampal-dependent behavioral paradigm used to identify schizophrenia-associated sensory processing deficits, was abnormal in C3H α7 knockout mice confirming that auditory gating also requires α7nAChR expression. Our studies highlight the importance of genetic background on the regulation of synaptic plasticity and could be relevant for understanding genetic and cognitive heterogeneity in human studies of α7nAChR dysfunction in mental disorders.